2020
DOI: 10.1101/2020.03.13.990564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The maturity in fetal pigs using a multi-fluid metabolomic approach

Abstract: In mammalian species, the first days after birth are an important period for survival and the rates of mortality before weaning are high. In pigs, the perinatal deaths average 20% of the litter, with important economic and societal consequences. Among the factors influencing piglet survival at birth, the maturity is likely to be one of the most important. Maturity can be defined as the outcome of complex mechanisms of intra-uterine development and maturation occurring during the last month of gestation. Here, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…This stage includes the Fourier transform stage, phase and baseline correction 61 , and a TSP referencing a 0.0 chemical shift as a reference standard (Supplementary Figure 5). Data analysis was performed using the ASICS package 62 , a package in the R programming language environment that can perform metabolomics analysis on 1 H NMR spectra to identify and quantify metabolites as referred to previous research 63,65 . This package could automatically identify and quantify metabolites in the NMR spectrum using a unique peak pattern (fingerprint) 59,62 .…”
Section: Metabolite Extractionmentioning
confidence: 99%
“…This stage includes the Fourier transform stage, phase and baseline correction 61 , and a TSP referencing a 0.0 chemical shift as a reference standard (Supplementary Figure 5). Data analysis was performed using the ASICS package 62 , a package in the R programming language environment that can perform metabolomics analysis on 1 H NMR spectra to identify and quantify metabolites as referred to previous research 63,65 . This package could automatically identify and quantify metabolites in the NMR spectrum using a unique peak pattern (fingerprint) 59,62 .…”
Section: Metabolite Extractionmentioning
confidence: 99%
“…Expression profiling of fetal liver of pig differing in utilization and partitioning of energy will point to metabolic pathways, which affect these physiological properties. In addition, the study of the metabolome during prenatal development is a promising way to identify and characterize parameters of piglet maturity at birth [28]. Ultrastructural studies revealed that the fetal pig liver exhibits specific hepatic metabolic competence and hepatopoietic activity at 40–80 dpc, followed by mainly glycogen accumulation [25].…”
Section: Discussionmentioning
confidence: 99%
“…This is not compatible with e cient and sustainable production. Last, several studies have showed that piglet maturity, de ned as the complete development allowing survival at birth, is likely to be an important determinant of subsequent survival [8][9][10][11]. Accordingly, piglet maturation and maximum fetal and placental growth, which occur towards the end of gestation, result in a nutritional burden of pregnancy for the mother.…”
mentioning
confidence: 99%